2010
DOI: 10.1002/adma.200901365
|View full text |Cite
|
Sign up to set email alerts
|

Mesocrystals—Ordered Nanoparticle Superstructures

Abstract: Mesocrystals are 3D ordered nanoparticle superstructures, often with internal porosity, which receive much recent research interest. While more and more mesocrystal systems are found in biomineralization or synthesized, their potential as material still needs to be explored. It needs to be revealed, which new chemical and physical properties arise from the mesocrystal structure, or how they change by the ordered aggregation of nanoparticles to fully exploit the promising potential of mesocrystals. Also, the me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

15
557
0
4

Year Published

2010
2010
2017
2017

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 572 publications
(576 citation statements)
references
References 146 publications
(261 reference statements)
15
557
0
4
Order By: Relevance
“…In recent years, new methods such as microwave-assisted hydrothermal 15 , bioinspired 16 and titration 17 methods have been developed to simplify the synthesis procedure and improve its efficiency. For instance, Zhou et al 6 prepared anatase TiO 2 mesocrystals by topotactically transforming NH 4 TiOF 3 crystals without changing their morphology. Our group has recently demonstrated that anatase TiO 2 mesocrystals can be synthesized via topotactic transformation using one-step direct annealing of a titanium solution as a precursor 7 .…”
mentioning
confidence: 99%
“…In recent years, new methods such as microwave-assisted hydrothermal 15 , bioinspired 16 and titration 17 methods have been developed to simplify the synthesis procedure and improve its efficiency. For instance, Zhou et al 6 prepared anatase TiO 2 mesocrystals by topotactically transforming NH 4 TiOF 3 crystals without changing their morphology. Our group has recently demonstrated that anatase TiO 2 mesocrystals can be synthesized via topotactic transformation using one-step direct annealing of a titanium solution as a precursor 7 .…”
mentioning
confidence: 99%
“…Mesocrystals (MC) are three-dimensional arrays of iso-oriented single-crystalline particles with an individual size between 1 -1000 nm. [1][2][3][4][5] Their physical properties are largely determined by structural coherence, for which the angular correlation between their individual atomic lattices and the underlying superlattice of nanocrystals (NC) is a key ingredient. 1,2 Colloidal NCs stabilized by organic surfactants have been shown to pose excellent building blocks for the design of synthetic MCs with tailored structural properties which are conveniently obtained by self-assembly of NCs from solution on a solid or liquid substrate by exploiting ligand-ligand 3 interactions.…”
mentioning
confidence: 99%
“…Using a structured organic matrix is an obvious mechanism for mesocrystal formation since the crystalline nanoparticles could align along the organic matrix [2], [19] . There are two possibilities for the formation of a mesocrystal: either the nanoparticles are formed first and then attach to the polymer and get oriented, or they nucleate directly on the organic matrix which could act as an oriented, heterogeneous nucleation site [20] . A large number of examples of ordered macromolecular structures are also known in the world of biomacromolecules.…”
Section: Wang Et Al Prepared a Variety Of Eufmentioning
confidence: 99%